2014
DOI: 10.1016/j.enbuild.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Using suite energy-use and interior condition data to improve energy modeling of a 1960s MURB

Abstract: Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the author manuscript from TSpace because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…64 Field studies have yielded similar results. 43,45,65 Back-draft of exhaust ventilation air is also possible in buildings with large interior stack pressures. 66 Uncontrolled inter-zonal airflows also affect where the MUA originates.…”
Section: Ventilationmentioning
confidence: 99%
“…64 Field studies have yielded similar results. 43,45,65 Back-draft of exhaust ventilation air is also possible in buildings with large interior stack pressures. 66 Uncontrolled inter-zonal airflows also affect where the MUA originates.…”
Section: Ventilationmentioning
confidence: 99%
“…• energy models struggle to account for the actual/future usage of a building and seldom account for occupancy schedules and levels; • accurate representations of occupant behaviour are not part of the typical modelling practices; • weather files provide historic and therefore inaccurate weather data used in the simulations [39]; and • studies have shown design-assist and compliance energy models prepared at the design stage are rarely verified or calibrated through as-built models, which provide predictions of energy performance based on what is actually built [16] (pp. [12][13][14].…”
Section: Assessing the Prediction Gapmentioning
confidence: 99%
“…While this work focuses on the modeled impacts of the proposed retrofits, this modeling was based on the results of both field monitoring and laboratory testing. The performance of the base case building-level model was determined from data collected from an occupied MURB over the course of one year [6]. Development of the model output processor was informed by laboratory testing of a suite-based ASHP operating in an enclosed balcony space.…”
Section: Modeling Approachmentioning
confidence: 99%
“…In previous work by the authors [6], a calibrated energy model was developed for a subject MURB constructed in 1968. The MURB on which this model was based exhibited many of the characteristics common to other post-war MURBs including exposed slab edges, pressurized-corridor make-up air supply, hydronic baseboard heating and no central air-conditioning.…”
Section: Building Modelmentioning
confidence: 99%
See 1 more Smart Citation